2015
DOI: 10.1016/j.ajpath.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Development of Blood and Lymphatic Endothelial Cells in Embryonic and Fetal Human Skin

Abstract: Blood and lymphatic vessels provide nutrients for the skin and fulfill important homeostatic functions, such as the regulation of immunologic processes. In this study, we investigated the development of blood and lymphatic endothelial cells in prenatal human skin in situ using multicolor immunofluorescence and analyzed angiogenic molecules by protein arrays of lysates and cell culture supernatants. We found that at 8 to 10 weeks of estimated gestational age, CD144(+) vessels predominantly express the venous en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Our data are consistent with reports of the Schuster‐ and Elbe‐Bürger group that show low numbers of macrophages, dendritic cells, and Langerhans cells in human fetal skin . In accordance with the data of Coolen et al and Schuster et al, no significant differences in the vascular network were observed either between fetal and adult skin. Furthermore, staining with early lineage marker CD45 showed significantly lower levels of CD45 + ‐cells in fetal skin compared to adult skin while fetal lymph nodes at this gestational age contained sufficient levels of CD45 + ‐cells comparable to adult lymph nodes.…”
Section: Discussionsupporting
confidence: 94%
“…Our data are consistent with reports of the Schuster‐ and Elbe‐Bürger group that show low numbers of macrophages, dendritic cells, and Langerhans cells in human fetal skin . In accordance with the data of Coolen et al and Schuster et al, no significant differences in the vascular network were observed either between fetal and adult skin. Furthermore, staining with early lineage marker CD45 showed significantly lower levels of CD45 + ‐cells in fetal skin compared to adult skin while fetal lymph nodes at this gestational age contained sufficient levels of CD45 + ‐cells comparable to adult lymph nodes.…”
Section: Discussionsupporting
confidence: 94%
“…Both LE and VE are present in 7 PCW fetal skin, earlier than previous studies using 8-10 PCW skin (26). Fetal lymphatic endothelial cells have lower expression of LYVE1, PDPN and CCL21 suggesting that they are functionally immature (Fig.…”
Section: Specialized Vascular Endothelium Mediates Leukocyte Traffickingmentioning
confidence: 54%
“…In summary, our data suggest that fetal skin and gut DC have the capacity to migrate through lymphatics and to lymph nodes from 16wk EGA, where they may interact with fetal T cells that are present in lymphoid organs from 10wk EGA16. The reason for the initiation of DC migration to the lymph nodes around 16wk EGA remains unclear: while the human lymphatic system is structurally complete by 8wk EGA, it may remain functionally immature for some time thereafter17.…”
mentioning
confidence: 83%